A Proposed E-learning Technology Management Model for Universities in Response to the COVID-19 Global Crisis - Mohamed Elsayed Elnaggar; Rasha Saad Sharaf (European Scientific Journal, ESJ, 2022)
The overall purpose of the study is to propose an e-learning technology management model that responds to the outbreak of the coronavirus disease 2019 (COVID-19) and that has led to the closure of almost all the world’s universities in 2020/2021, leading to many complications in arranging for remote teaching and learning processes. The basic design of the study included the analysis of different technology management models in terms of scope and integration. In addition to a survey directed to several international higher education and e-learning experts as well as a thematic analysis for qualitative data obtained from experts’ comments and views. The major findings, from both quantitative and qualitative analysis, structured the design of the model that has the advantage of mobilizing all university resources towards the achievement of intended learning outcomes. It focuses on six domains for elearning technology management: a) planning, b) governance and administration, c) capacity building, d) development, e) interactive teaching and learning, and f) assessment and evaluation. Hence, the proposed elearning technology management model provides better access, and more economic management of resources, and maximizes return on investment with better learning outcomes at higher education institutions.